Construções discursivas do trabalho em Crônicas da vida operária de Roniwalter Jatobá - Marques, Guiosepphe Sandri (2015)
This dissertation analyzes the discursive constructions on work in four tales of Roniwalter Jatobá (1979): “The Left hand”; “Accommodation”; “The red cloth”; “Workers “. Jatobá creates a critical vision of work in relation to migrant workers unsuitable in São Paulo during the 1960s and 1970s. Interpret and discuss the work of vision in Jatobá is the objective of the dissertation. This dissertation part of a multidisciplinary perspective of Literature, Sociology, Social History and Philosophy of language. The discussion on the language and work as constitutive of the social considers the contributions of several authors that question what is the work and the language. In the area of language, the contributions of Bakhtin/Voloshinov (2004) help think critically about the social and ideological construction of the existing awareness and dialogical relations in any discursive construction. In the area of work, the contributions of Marx (2013), Lukács (2012; 2013), Engels (2013), Gorz (2007), Lafargue (1980) and Sennett (2006) help to question what is the work and its importance for today. The brief discussion of some of the discourses in the work of the twentieth century Brazil comes from the Social Work History, De Decca (1995), Fontes (2004), Mattos (2009) e Chalhoub (2012). The study Roniwalter Jatoba speech context more the set of his works and his biography were essential for the analysis of literary corpus. The subject of the work, from the perspective of literary discourse, brings another critical point of view from the migrant worker himself. For this, Jatoba explores the worker's uniqueness in its human dimension in and out of work, the place of origin and destination, in dreams and frustrations created by the migrant worker unsuitable in São Paulo. In a social perspective and politically committed, it is concluded that Crônicas da vida operária allows other critical interpretations of the work and the urban worker in São Paulo of the 1960s and 1970s.